Celebrate Discovery - Corbett, Glenn J. (The Biblical archaeology review, 2022)
This year marked the anniversaries of some of the most important archaeological discoveries from the world of the Bible. We celebrated 200 years since Egyptian hieroglyphs were first deciphered, the centennial of the discovery of King Tut’s tomb, and perhaps most significantly for biblical archaeology, the 75th anniversary of the discovery of the Dead […]